2008
DOI: 10.1111/j.1462-5822.2008.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella catarrhalis lipooligosaccharide selectively upregulates ICAM-1 expression on human monocytes and stimulates adjacent naïve monocytes to produce TNF-α through cellular cross-talk

Abstract: SummaryTo elucidate the role of Moraxella catarrhalis lipooligosaccharide (LOS) in otitis media with effusion (OME), the effects of LOS on adhesion antigens of human monocytes were investigated. M. catarrhalis LOS selectively enhanced intercellular adhesion molecule 1 (ICAM-1 or CD54) expression on human monocytes by significantly increasing both the surface expression intensity and the percentage of ICAM-1 + cells. ICAM-1 upregulation on human monocytes by the LOS required surface CD14, TLR4, NF-kB p65 and c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
(78 reference statements)
1
21
0
Order By: Relevance
“…The M. catarrhalis lipooligosaccharides (LOS) (68) and the outer membrane protein UspA1 might be involved in stimulating the secretion of IL-8 in vitro (57), and MID/Hag might be involved in B-cell activation (47,67). Importantly, serum samples from COPD patients who had recently cleared M. catarrhalis infection are reactive to M. catarrhalis LOS (53) and MID/Hag (40), indicating that M. catarrhalis extracellular components may contribute to the production of inflammatory disease.…”
Section: Figmentioning
confidence: 99%
“…The M. catarrhalis lipooligosaccharides (LOS) (68) and the outer membrane protein UspA1 might be involved in stimulating the secretion of IL-8 in vitro (57), and MID/Hag might be involved in B-cell activation (47,67). Importantly, serum samples from COPD patients who had recently cleared M. catarrhalis infection are reactive to M. catarrhalis LOS (53) and MID/Hag (40), indicating that M. catarrhalis extracellular components may contribute to the production of inflammatory disease.…”
Section: Figmentioning
confidence: 99%
“…It can potentially induce excessive inflammation via cellular cross-talk [11]. Unlike the outer membrane proteins such as MID, UspA, and CopB that show a great plasticity in their antigenicity [6], [23], the structures of LOS are highly conserved within each of the three serotypes of M. catarrhalis [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…catarrhalis . Being a major virulence factor of M. catarrhalis, LOS induces excessive inflammation via a Toll-like receptor 4 (TLR4) and CD14 dependent pathway [11]. The structures of LOS are conserved among 95% of known M. catarrhalis strains and clinical isolates [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Frick et al (20) and Humlicek et al (26) found that adherence of nontypeable H. influenzae to respiratory epithelial cells rapidly induced ICAM-1 expression, a process that they hypothesized would facilitate the recruitment of neutrophils to sites of nontypeable H. influenzae infection. Xie and Gu demonstrated that leukocyte recruitment mediated by enhanced ICAM-1 levels after M. catarrhalis infection may also result in increased bacterial adhesion to the respiratory tract (52). In the current study, although there is no direct evidence to illustrate that the enhanced ICAM-1 level has promoted neutrophil recruitment to the middle ear, the literature and the fact that the elevation of serum sICAM-1 levels in children with AOM positive for bacteria in MEF suggest that the intercellular adhesion molecules are upregulated during middle ear inflammation and that the increased ICAM-1 levels may contribute to innate immune responses through increasing leukocyte recruitment to the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that ICAM-1 is endogenously expressed on various cell types and makes possible reversible adhesion and signal transduction between cells, processes critical to T-cell development. Increased levels of ICAM-1 promote cell-cell interactions, playing a critical role in leukocyte recruitment and leading to prolonged and, sometimes, excessive inflammation (52).…”
Section: Discussionmentioning
confidence: 99%